Analisis Pengelolaan Wakaf Produktif dalam Efektivitas Pemberdayaan Sosial Ekonomi Masyarakat Kota Medan - Kausar, Al; Soemitra, Andri; Batubara, Chuzaimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The purpose of this study was to examine and find out the management of waqf in an effort to effectively empower the socio-economic community of the city of Medan. The type of research used is field research (field research) with a qualitative descriptive approach which describes data and information based on data obtained in the field. In this case the author conducted a case study on 3 foundations, namely the H. Anif Foundation, the Al-Jihad Mosque Foundation , and the Ar-Raudatul Hasanah Foundation. The results of the research showed that the implementation of productive waqf management in Medan was a case study of 3 foundations, only 2 foundations had productive waqf and 1 still emphasized infaq and alms. 2 foundations that have productive endowments emphasize social and economic aspects.